2012
DOI: 10.1038/nrgastro.2011.274
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the mystery of pain in chronic pancreatitis

Abstract: Chronic pancreatitis is typically a painful condition and it can be associated with a severe burden of disease. The pathogenesis of pain in this disorder is poorly understood and its treatment has been largely empirical, often consisting of surgical or other invasive methods, with an outcome that is variable and frequently unsatisfactory. Human and experimental studies have indicated a critical role for neuronal mechanisms that result in peripheral and central sensitization. The pancreatic nociceptor seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 106 publications
0
61
0
7
Order By: Relevance
“…Human and experimental studies have indicated a critical role of neuronal mechanisms that result in peripheral and central sensitization. [1][2][3] The nociceptive sensitization, literally meaning sensitization to noxious stimuli, begins with the primary afferent nociceptor, a nerve whose cell body lies in the dorsal root ganglia (DRG). DRG is located next to the spinal cord and has 2 branches: a long peripheral one terminating in the target tissue and a shorter central process that ends in the dorsal horn of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Human and experimental studies have indicated a critical role of neuronal mechanisms that result in peripheral and central sensitization. [1][2][3] The nociceptive sensitization, literally meaning sensitization to noxious stimuli, begins with the primary afferent nociceptor, a nerve whose cell body lies in the dorsal root ganglia (DRG). DRG is located next to the spinal cord and has 2 branches: a long peripheral one terminating in the target tissue and a shorter central process that ends in the dorsal horn of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no single remedy for pain relief exists and an optimal pain treatment can only be achieved on the basis of a better understanding of the pain mechanisms underlying pain in the individual patient [2] . While, the focus of pain origin in CP historically has been on the pancreatic gland, assuming pain to originate in the pancreas or its surrounding organs, recent findings indicate that both peripheral and central pain processing are abnormal in CP patients [1,3] . Various mechanisms responsible for the altered pain processing have been proposed, including pancreatic neuropathy and neural remodeling [4,5] , sensitization of neurons in the spinal cord and the brain [6,7] , reorganization of the brain areas involved in visceral pain processing [8] and alterations in descending pain control from the brainstem and other supraspinal structures [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a prominent symptom in chronic pancreatitis (CP), but its underlying mechanisms are incompletely under-stood and probably multifactorial [1] . Thus, no single remedy for pain relief exists and an optimal pain treatment can only be achieved on the basis of a better understanding of the pain mechanisms underlying pain in the individual patient [2] .…”
Section: Introductionmentioning
confidence: 99%
“…This led to a dispute between researchers believing in the so called "plumbing" and "wiring" hypotheses (51). Those that advocate for the plumbing hypothesis based their findings that on the assumption that pain is generated by increased pressure in the pancreatic duct or in the pancreatic parenchyma.…”
Section: Pain Pathogenesismentioning
confidence: 99%
“…Abdominal pain is present in most patients and the primary cause of hospitalization (51). Pancreatic pain is characteristically described as a constant, severe, dull, epigastric pain that often radiates to the back and typically worsens after meals.…”
Section: Characterization Of Painmentioning
confidence: 99%